2019
DOI: 10.1007/s42452-019-0873-x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium critical level in soil for Teff (Eragrostis tef (Zucc.) Trotter) grown in the central highland soils of Ethiopia

Abstract: Responses to potassium (K) fertilizer are reported in different parts of Ethiopia in recent years, contrary to the general perception that K fertilizer was not necessary on the soils. However, use of adequate K level for maximum economic yield is possible only when soil test data are calibrated against response curve for a given crop and soil type. This pot trial was conducted to calibrate K soil test with the response of teff (Eragrostis tef (Zucc.)) at application of increasing levels of K. Random soil sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
0
5
1
1
Order By: Relevance
“…(2017) reported that the application of an excessive amount of K can cause yield decline due to the antagonistic effect of the same on Mg. In contrast to this study, Mulugeta et al. (2020) reported a significant increase in tef grain and straw yields due to the application of K fertilizer in 67% of the tested locations covered by Vertisols.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…(2017) reported that the application of an excessive amount of K can cause yield decline due to the antagonistic effect of the same on Mg. In contrast to this study, Mulugeta et al. (2020) reported a significant increase in tef grain and straw yields due to the application of K fertilizer in 67% of the tested locations covered by Vertisols.…”
Section: Resultscontrasting
confidence: 99%
“…(2011) who reported that K levels between 250 and 800 mg kg −1 are categorized as high. Based on the results of a pot experiment, Mulugeta et al. (2019) also reported K critical level of 210 mg kg −1 following the Mehlich-3 method ( Mehlich, 1984 ) for tef to achieve 85% relative biomass yield level in Vertisols of Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of soil pH (H2O) ranged from 5.4 to 7.4 showing that most of the soils were slightly acidic to neutral in reaction. Based on the K critical levels generated for teff (Mulugeta et al, 2019), which categorized the Mehlich-3 K of <210, 210-280, 280-500, and >500 mg kg -1 as low, medium, high and very high respectively; the K values of the study soils were in the range from low to very high. On the other hand, according to EthioSIS (2013, 2016) which categorized Mehlich-3 K values of < 90, 190-600, 600-900 and >900 mg kg -1 as very low, low, optimum, high and very high; the K status of the soils are in the range of low to medium.…”
Section: Physical and Chemical Properties Of The Soilsmentioning
confidence: 99%
“…Because of limited knowledge on the K dynamics in Ethiopian soils and the absence of a remarkable response to K application, there has been sweeping generalization on K status in Ethiopian soils and as a result, there has not been adequate focus given to potassium in the national fertilizer scheme (Mesfin, 2007). Recently, however, a highly negative K balance and deficiency as well as responses to application of K fertilizer is reported in different parts of Ethiopia, contrary to the general perception that K fertilizer was unnecessary for the soils (EthioSIS, 2016;Mulugeta et al, 2019). So, site-specific applications of K-fertilizers would help to gain more responses from crops.…”
Section: Critical Levels Of Soil Nutrients and Their Managementmentioning
confidence: 99%